113k views
2 votes
Whats is rusult of : ( - 2x² )³ . ( - 3x )²

User Stantona
by
4.8k points

2 Answers

2 votes

Answer:


- 72x^(8)

Explanation:


( - 2x^2 )^3 * ( - 3x )^2

Distribute the exponents to the brackets.


( - 2^3x^(2* 3) ) * ( - 3^2x^2 )


( - 2^3x^(6) ) * ( - 3^2x^2 )


( - 8x^(6) ) * ( 9x^2 )


- 8 * x^(6) * 9 * x^2


- 8 * 9 * x^2 * x^(6)

Multiply like terms and add exponents with same bases.


- 72 * x^(2+6)


- 72 * x^(8)

User Teoreda
by
4.7k points
5 votes

Answer:


-72x^8

Explanation:

=>
(-2x^2)^3*(-3x)^2

=>
-8x^6*9x^2

=>
(-8*9) *(x^6x^2)

When bases are same powers are to be added

=>
(-72)(x^(6+2))

=>
-72x^8

User Lemiorhan
by
5.3k points